Comparison of Bunch Number of Commercial Oil Palm Varieties were 10-11 years old On Tha Sae District, Chumpon Province - Krualee, Sudanai; Puttakan, Thammasak; Buakhaw, Sathit; Rattanasupha, Wutthisak; Wongpisal, Pimchana (YRU Journal of Science and Technology, 2024)
The problem affecting palm oil production is the difference in the number of palm bunches for each species. Species with more bunches can produce large quantities of palm oil. This is caused by genetic differences between oil palm species. The objective of this research was to compare the number of commercial oil palm bunches aged 10-11 years in 2017 and 2018. A completely randomized design (CRD) was planned. The experimental items were: Oil palm varieties, 10 years old, totaling 8 varieties, namely Surat Thani 1, Surat Thani 2, Surat Thani 3, Surat Thani 4, Surat Thani 5, Surat Thani 6, Pao Rong, and Lame. Data were collected for each variety on the number of bunches of 10 trees. Results of the experiment found that different oil palm varieties in different harvest years result in different numbers of bunches per tree per year. When analyzing the main influences as additive and multiplicative interactions (AMMI), it was found that only one principal component analysis (Principal Component Analysis, PCA1) was able to separate all elements of the interaction between oil palm variety and harvest year. Throughout the 2 year period of data collection the Surat Thani 3 oil palm variety, it was the most stable with a value of -0.13 for the Lame oil palm variety. The least stable has a PCA1 value of 1.11. When considering specific adaptations, it was found that The Surat Thani 6 oil palm variety gave the highest number of bunches per year, equal to 18.30 bunches per year, while in 2017, the Surat Thani 5 oil palm gave the highest number of bunches per year. In 2018, it was equal to 15.10 bunches per year. Therefore, the oil palm varieties that should be planted are Surat Thani varieties 3, 5 and 6, which have suitable environmental conditions. There must be an even distribution of rainwater.